Color and COD Removal from Real Textile Wastewater using Nanoscale Zero-Value Iron (nZVI) - Tepe, Ozlem; Tunc, Muslun; Hanay, Ozge (Gazi Univ, 2021)
Nanoscale zero-value iron (nZVI) has a high specific surface area and significant abilities to reduce contaminants. In this study, the removal of color and COD from real textile wastewater was studied by nZVI particles. A series of experiments were conducted to evaluate the effect of operational parameters such as solution pH, nZVI dosage and temperature on color and COD removal. The results showed that the color and COD removals mainly depend on solution pH. The color removal efficiencies were 96.3% at 436 nm, 97.8% at 525 nm and 98.0% at 620 nm, respectively at nZVI dosage of 0.3 g/L and initial pH of 3 after 180 minutes of reaction time at 25 OC. Moreover, the maximum COD removal efficiency obtained under these conditions was 86%.
Keywords: Color and COD removal; Nanoscale zero-valent iron particles (nZVI); Real textile wastewater; Wastewater treatment